PROFIL TINGKAT KECEMASAN PASIEN TUBERKULOSI PARU DI IRINA C BLU RUMAH SAKIT PROF.dr.R.D.KANDOU MANADO - Maria Terok; Tinneke Tololiu; Juliv Podung (Jurnal Ilmiah Perawat Manado (Juiperdo), 2013)
Anxiety or anxiety often experienced by virtually all humans are subjective in nature and pathological . The feeling of fear is characterized by diffuse , unpleasant , often accompanied by autonomic symptoms such as headache , sweating , palpitations and excessive gelisah.Respon emotions experienced by any patient with pulmonary tuberculosis because of the threat or danger of the disease that can cause distress and disruption activities of daily living even kematian.Tb Lung is the second leading cause of death in Indonesia after the 2010 Jantung.Tahun disease incidence rate of TB adalah189 / 100,000 population and population mortality 27/100.000 ( Sudoyo , 2007) The purpose of this study was to determine the profile level Pulmonary tuberculosis in patient anxiety Irina C BLU RSU . Prof . Dr. . R. D. Kandou Manado . The study was descriptive , to describe the anxiety level of TB patients Paru.Penelitian held in July of 2012.Populasi research is Selufuh Pulmonary tuberculosis patients totaling 25 people who were taken by means of purposive sampling.Instrumen data collection using questionnaires according to the Hamilton Rating Scale For Anxiety ( HRS - A ) to determine the level of patient anxiety paru.Pengolahan TB of data was done manually by using a percentage formula The results showed that of the 25 respondents obtained mild anxiety level 1 respondent ( 4 % ) , anxiety was 1 respondent ( 4 % ) , severe anxiety 11 respondents ( 44 % ) , and panic 12 respondents ( 48 % ) . Based on the results of this study concluded that the level of anxiety experienced by patients with pulmonary TB is the most severe ( 44 % ) and panic ( 48 % ) , summed as much as 92 % . This occurs because the patient gave a negative magna and that excessive pulmonary TB disease is a disease that is severe and difficult to disembuhkan.Padahal Lung disease can be cured so long as the patient's regular medical treatment . It is therefore suggested to the officer that there was in theHospital provide health education to patients and families clearly about the care and treatment of patients who should be run regularly to get the necessary treatment kesembuhan.Disamping psychologically to cope with the anxiety response experienced by patients and their families . Increase coping mechanisms to deal with anxiety